Community Involvement in Agritourism: A Participatory Approach to Rural Sustainable Development - Mappe, Ulfa Utami; Amandaria, Riri; Mario, Mario (LPPM Universitas Madako Tolitoli, 2024)
Agritourism is a form of tourism that integrates the agricultural sector with tourism activities, aims to provide educational and recreational experiences for visitors and improve the welfare of rural communities through economic diversification. In Indonesia, the potential for agritourism is enormous thanks to the abundant natural and agricultural wealth. The active participation of local communities in the management of agritourism is the main key to the sustainability and success of this programme. Community participation can be realised through involvement in programme planning, implementation and evaluation, providing positive economic and social impacts. Support from various parties such as the government, private sector, and non-governmental organisations is essential to ensure the sustainability of agritourism. This research highlights the management of Tabarano Agro Hill in Tabarano Village, East Luwu Regency, showing how local community participation in agritourism management contributes significantly to sustainable rural development. The research method used was a descriptive qualitative approach, with data collection through in-depth interviews, observation, and documentation. The results showed that community participation in various aspects of management, including decision-making, programme implementation, environmental maintenance, and marketing, improved the quality and attractiveness of agritourism, and provided sustainable economic, social, and environmental benefits for the local community.